2022
DOI: 10.3390/mi13050744
|View full text |Cite
|
Sign up to set email alerts
|

Darcy-Forchheimer Flow of Water Conveying Multi-Walled Carbon Nanoparticles through a Vertical Cleveland Z-Staggered Cavity Subject to Entropy Generation

Abstract: To date, when considering the dynamics of water conveying multi-walled carbon nanoparticles (MWCNT) through a vertical Cleveland Z-staggered cavity where entropy generation plays a significant role, nothing is known about the increasing Reynold number, Hartmann number, and Darcy number when constant conduction occurs at both sides, but at different temperatures. The system-governing equations were solved using suitable models and the Galerkin Finite Element Method (GFEM). Based on the outcome of the simulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…According to [9], there is a link between respiratory illness, environmental exposure, and nano-sized particles. [10] recently published the results of another investigation on the addition of multi-walled carbon nanoparticles to the dynamics of water within a vertical Cleveland Z-staggered cavity, which demonstrated that raising the Reynold number increases the inertial force. [11] revealed that an optimal mix of nanoparticles is another essential feature in increasing thermal transfer in an annular geometry comprising nanoliquids with variably heated borders.…”
Section: Background Informationmentioning
confidence: 99%
“…According to [9], there is a link between respiratory illness, environmental exposure, and nano-sized particles. [10] recently published the results of another investigation on the addition of multi-walled carbon nanoparticles to the dynamics of water within a vertical Cleveland Z-staggered cavity, which demonstrated that raising the Reynold number increases the inertial force. [11] revealed that an optimal mix of nanoparticles is another essential feature in increasing thermal transfer in an annular geometry comprising nanoliquids with variably heated borders.…”
Section: Background Informationmentioning
confidence: 99%
“…Two proven methods include enhancing free convection heat transmission inside the cavity by adding nanoparticles to the fluid and producing turbulence flow. Because of the fluid’s altered viscosity and thermal conductivity, the presence of nanoparticles in the fluid causes an abnormal treatment of nanofluids [ 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, various studies have been undertaken on double-diffusion convection inside a lid-driven container loaded with normal fluids or nanofluids with varied temperature settings. A few relevant past studies have been provided here [ 1 , 2 , 3 , 4 ]. Zakaria et al [ 5 ] explored the magneto-convection flow generated by the lid in a chamber with two curved edges; here, the bottom side was partly heated and loaded with a hybrid nanofluid composed of Al2O3-Cu/water.…”
Section: Introductionmentioning
confidence: 99%